Exploring the Connections Between Grip Strength, Nutritional Status, Frailty, Depression, and Cognition as Initial Assessment Tools in Geriatric Rehabilitation—A Pilot Study - Amalia Teodora Vancea Nemirschi; Andreea Alexandra Lupu; Kamer-Ainur Aivaz; Mădălina Gabriela Iliescu; Michel Deriaz; Mircea Marzan; Luiza Spiru (Medicina)
Background and Objective: In the context of the rapidly aging global population, the older adult vulnerability poses a significant challenge for public health systems. Frailty, cognitive and nutritional status, depression, and grip strength are essential parameters for staging the vulnerability of older adults. The objective of this study is to identify a rapid but multidimensional geriatric assessment tool that can enhance the rehabilitation process for older adults, tailored to their specific needs. Materials and Methods: This pilot study examines the relationships between grip strength, nutritional status, frailty, depression, and cognition in a group of 80 older adults with a mean age of 69.6 years, 49 male and 31 female, using standardized geriatric scales and digital grip strength measurements. The study employed a digital dynamometer, a portable and reliable tool that facilitated quick and accurate grip strength measurements. Results: The analysis revealed significant correlations among the parameters. Greater grip strength was associated with better cognitive performance (r = 0.237, p = 0.034) and improved nutritional status (r = 0.267, p = 0.016), while it was inversely related to frailty (r = −0.313, p = 0.005). Nutritional status also played a key role, showing an inverse relationship with frailty (r = −0.333, p = 0.003) and depression levels (r = −0.248, p = 0.027). Furthermore, frailty and depression were strongly interconnected, with those experiencing higher frailty levels also displaying more severe depressive symptoms (r = 0.545, p < 0.001). Marital status was also relevant: married participants exhibited higher grip strength, lower frailty, and fewer depressive symptoms, suggesting that social support positively influences both physical and mental health in older adults. Conclusions: These findings not only emphasize the need for integrated care approaches that simultaneously address physical health, nutrition, and cognitive function, but also provide a foundation for the development of a rapid and multidimensional assessment protocol, which consists of using a digital dynamometer and four geriatric scales. Such a tool could play a crucial role in the early detection of frailty syndrome and guide the implementation of multidisciplinary, tailored therapeutic strategies aimed at preserving the autonomy and improving the quality of life of older adults.